2007
DOI: 10.1185/030079907x187892
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of the size of low-density-lipoproteins and the modulation of subclasses by fibrates

Abstract: Among the different agents, fenofibrate has been found to be particularly effective in modulating LDL size and subclasses in patients at higher cardiovascular risk, such as those with type 2 diabetes or the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Although this effect was mainly due to FENO, EZE monotherapy also produced a small, nonsignificant increase in LDL peak particle size relative to placebo. This change in LDL size has been previously demonstrated with fibrates [14] and is consistent with the dramatic decrease in the proportion of patients with the LDL pattern B phenotype after treatment with FENO + EZE and FENO. As previously published, the proportions of patients exhibiting LDL pattern B at baseline were 69.5%, 77.6%, 74.7%, and 74.5% in the placebo, EZE, FENO, and FENO + EZE groups, respectively [1].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although this effect was mainly due to FENO, EZE monotherapy also produced a small, nonsignificant increase in LDL peak particle size relative to placebo. This change in LDL size has been previously demonstrated with fibrates [14] and is consistent with the dramatic decrease in the proportion of patients with the LDL pattern B phenotype after treatment with FENO + EZE and FENO. As previously published, the proportions of patients exhibiting LDL pattern B at baseline were 69.5%, 77.6%, 74.7%, and 74.5% in the placebo, EZE, FENO, and FENO + EZE groups, respectively [1].…”
Section: Discussionsupporting
confidence: 89%
“…We previously demonstrated that coadministration of FENO + EZE was well tolerated for up to 52 weeks and produced complementary, favorable effects on LDL-C, TG, and HDL-C in patients with mixed hyperlipidemia [1,2]. Although the influence of fibrates on lipoprotein subfractions and LDL particle size has been characterized previously [14], the effects of EZE or the coadministration of FENO + EZE on lipoprotein subfractions have not been previously evaluated in patients with mixed hyperlipidemia. The present report provides the first information on the effects of FENO and EZE alone compared with their use in combination on cholesterol levels in lipoprotein subfractions assessed by the VAP II method.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the therapeutical modulation of low HDL-cholesterol and high triglycerides significantly reduce cardiovascular risk [3] and lipid-lowering agents are also effective in reducing levels of small, dense LDL [26][27][28]. Dietary management is also of importance in such category of high-risk subjects [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, strong variations existed between the different fibrates. Fenofibrate appeared to be more effective compared with bezafibrate, gemfibrozil and ciprofibrate [16]. As new fibrates proved to be more effective in reducing triglyceride with little adverse drug reaction, the basic technology for their preparation and combination developed rapidly.…”
Section: Discussionmentioning
confidence: 99%